The Analysis of Critical Thinking Achievement of Primary School Students Taught by Online Learning - Rusdiyana Rusdiyana; Dyah Rini Indriyanti; Hartono Hartono; Wiwi Isnaeni (Universitas Negeri Semarang, 2022)
Abstrak. The science learning at primary schools for learners should refer to the Ministerial Regulation of Cultural and Educational Ministry Number 24 about Core Competence and Basic Competence. This research aims to: 1). Analyze the critical thinking skills of primary school students taught with online learning, and 2) analyze the cause of critical thinking achievement problems in science learning at primary school. This qualitative descriptive research took the data from the in-depth interview. The researchers promoted the research at four primary schools in Banjarbaru on December 1, until December 30, 2021. The researchers took the data source from the Quality Assurance Agency of Education Department in Southern Borneo, the school advisors, the principals, the primary school teachers, the fourth graders, and the parents. The applied analysis was Miles & Huberman (2014), starting from the data reduction, data display, and data verification. The results showed most teachers applied science learning online but the learning could not reach the critical thinking target for the learners. The fact predicting factors of the problems were 1). Learning scenario plan without Core Competence analysis and without considering the Core Competence, 2) The problem of designing the online learning, and 3) The mindsets of the teachers and principals about the learning objectives to accomplish the curriculum materials instead of reaching the core competence.